Plasma Granzyme B in ST Elevation Myocardial Infarction versus Non-ST Elevation Acute Coronary Syndrome: Comparisons with IL-18 and Fractalkine - Hala O. El-Mesallamy; Nadia M. Hamdy; Adel K. El-Etriby; Eman F. Wasfey (Mediators of Inflammation)
Objective. The proapoptotic protein, granzyme B (GZB), was identified as a contributor to the atherosclerotic plaque instability and recently as inflammatory activator. We studied the release kinetics of GZB and other markers of inflammation such as high sensitivity C reactive protein (hsCRP), interleukin 18 (IL-18), and fractalkine (FKN) in the early phase after acute cardiac events in different ACS subgroups. Methods. Thirty-six nondiabetic patients with ACS were compared to 12 control subjects. According to ACS diagnosis, the patients were classified into 22 patients with ST elevation myocardial infarction (STEMI) and 14 patients with non-ST elevation myocardial infarction or unstable angina (NSTEMI/UA). Blood samples were taken on day 1 (day of onset) and day 3 to measure hsCRP, IL-18, FKN, and GZB by ELISA. Results. Patients with ACS showed significantly higher GZB, IL-18, and FKN levels than the controls. STEMI group showed significantly higher GZB levels than NSTEMI/UA group. On day 3, FKN levels displayed a significant decrease, while GZB levels were significantly increased. IL-18 levels were more or less constant. GZB levels were positively correlated with IL-18 (, ) and FKN (, ). Conclusions. Unlike IL-18 and FKN, plasma GZB may be a marker of ACS disease severity.